Natural durability of five tropical wood species in field decay tests - Gomes Batista, Felipe; De Melo, Rafael Rodolfo; de Medeiros, Dayane Targino; Goes Lopes, Pedro Jorge; Gatto, Darci Alberto (Maderas. Ciencia y Tecnología, 2022)
Measuring the natural resistance of wood is fundamental for proper use. The natural durability of five tropical wood species was investigated by field decay testing during exposure for 360 days. Wood logs (length of 0,5 m; diameter of 8 cm - 12 cm) were used in this study. The mass loss and decay index were calculated and visual analysis during the exposure time was performed for all samples. The samples presented evidence of two different groups concerning natural durability. The species in the first group (Mimosa caesalpiniifolia, Mimosa ophthalmocentra, and Mimosa tenuiflora) showed the highest resistance to biodeterioration, better or similar performance compared to treated eucalyptus wood (as control). The other group (Aspidosperma pyrifolium and Cordia oncocalyx) had lower natural resistance in outdoor service, being more susceptible to decay. In general, the wood of the first group is indicated for outdoor uses that require medium or prolonged exposure, such as timber stakes and fence posts.